2014
DOI: 10.1016/j.foodchem.2013.06.133
|View full text |Cite
|
Sign up to set email alerts
|

Iron-binding properties of sugar cane yeast peptides

Abstract: The extract of sugar-cane yeast (Saccharomyces cerevisiae) was enzymatically hydrolysed by Alcalase, Protex or Viscozyme. Hydrolysates were fractionated using a membrane ultrafiltration system and peptides smaller than 5kDa were evaluated for iron chelating ability through measurements of iron solubility, binding capacity and dialyzability. Iron-chelating peptides were isolated using immobilized metal affinity chromatography (IMAC). They showed higher content of His, Lys, and Arg than the original hydrolysates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…Furthermore, de la Hoz et al (2014) revealed that enzymatic hydrolysis of the extract of sugar-cane yeast (Saccharomyces cerevisiae) by Viscozyme yielded iron-binding peptides, which increased iron bioavailability. They analyzed iron bioavailability through the iron dialyzability (i.e., the amount of soluble and stable iron until intestinal digestion) during in vitro digestion.…”
Section: Anti-anemic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, de la Hoz et al (2014) revealed that enzymatic hydrolysis of the extract of sugar-cane yeast (Saccharomyces cerevisiae) by Viscozyme yielded iron-binding peptides, which increased iron bioavailability. They analyzed iron bioavailability through the iron dialyzability (i.e., the amount of soluble and stable iron until intestinal digestion) during in vitro digestion.…”
Section: Anti-anemic Effectmentioning
confidence: 99%
“…They analyzed iron bioavailability through the iron dialyzability (i.e., the amount of soluble and stable iron until intestinal digestion) during in vitro digestion. They further isolated the peptides through immobilized metal affinity chromatography (IMAC) and showed that His, Lys, and Arg were more prevalent in these anti-anemic peptides (De la Hoz et al, 2014).…”
Section: Anti-anemic Effectmentioning
confidence: 99%
“…Also, it has been found that yeast protein has high proportion of hydrophobic and basic residue, hence can be considered as a source of ACE inhibitor and antioxidant peptides (de la Hoz et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cys, Met, His, Gln, Glu, Lys, Arg and Ser within the sequences of peptides are believed to contributing the metal chelating activity (Torres-Fuentes et al 2011;Wu et al 2012;Xia et al 2012;De la Hoz et al 2014). Sulph-hydryl (Cys) groups, carboxylate groups (Asp, Glu) and nitrogen-rich imidazole group of the His act as principal site for iron binding (Zachariou and Hearn 1996;Seth and Mahoney 2001;Huang et al 2011).…”
Section: Introductionmentioning
confidence: 99%